1990
DOI: 10.1002/bjs.1800770140
|View full text |Cite
|
Sign up to set email alerts
|

Selective postoperative radioactive iodine treatment of thyroid carcinoma

Abstract: (SURGERY 7989; From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
5

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
2
11
0
5
Order By: Relevance
“…Systematic lymphadenectomy or scintigra- phy after remnant ablation would therefore not be necessary for definitive N staging. Extensive lymph node involvement is seen in cases with diffuse lung metastases [9,17,18]. In young patients (TNM stage II) the tumors are usually curable with radioiodine [17,18] (one patient in our series).…”
Section: Papillary Carcinomamentioning
confidence: 96%
See 2 more Smart Citations
“…Systematic lymphadenectomy or scintigra- phy after remnant ablation would therefore not be necessary for definitive N staging. Extensive lymph node involvement is seen in cases with diffuse lung metastases [9,17,18]. In young patients (TNM stage II) the tumors are usually curable with radioiodine [17,18] (one patient in our series).…”
Section: Papillary Carcinomamentioning
confidence: 96%
“…In some patients the course is favorable even with limited therapeutic measures, whereas other patients die of the tumor despite radical therapy [1][2][3][4][5][6][7]. In some, however, radical therapy does improve outcome in terms of cure, curable recurrence, serious recurrence, and death from the tumor [2,3,[5][6][7][8][9]. Some studies indicate that patients can be selected for less radical procedures without incurring the risk of a fatal outcome and without recurrence being a major problem [2,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Mazzaferri and Jhiang [5] have concluded that near-total thyroidectomy followed by radioiodine therapy plus thyroid hormone administration confers a distinct outcome advantage for tumors 15 mm or more that are not initially metastatic to distant sites. However, McHenry et al [13] have found no recurrences in patients with DTC without local tumor extension or regional or distant metastases who were treated with postoperative thyroid hormone therapy, and they have recommended that radioactive therapy be omitted for these patients (Table III). Varma et al [14] also have reported no significant difference in death rates between patients under 40 years of age treated with radioiodine therapy versus those treated with surgery alone, while the former group had a significantly lower death rate than the latter in patients 40 years of age and older (Table III).…”
Section: Radioiodine Treatment and Thyroid Hormone Replacementmentioning
confidence: 96%
“…However, there are considerable controversies concerning not only the extent of thyroidectomy but also the indications for, and the extent of, cervical lymph node dissection [11], although surgical resection is the most effective treatment for DTC. Moreover, there is disagreement about the prophylactic use of radioiodine therapy [12][13][14]. Although no prospective studies have been performed evaluating the efficacy of surgical treatment and postoperative radioiodine therapy [15,16], the therapeutic approach to DTC should be unified to a more rational approach.…”
Section: Introductionmentioning
confidence: 99%